Healthcare students' vaccination status, knowledge, and protective behaviors regarding hepatitis B: a cross-sectional study in Turkey - Ayla Acikgoz; Selda Yoruk; Aygul Kissal; Şebnem Yildirimcan Kadicesme; Emine Catal; Gonca Kamaci; Fatma Ersin (Taylor & Francis Group, 2021)
Aim We aimed to determine the vaccination status, knowledge, and protective behaviors of healthcare students related to hepatitis B and to examine the related factors. Method This cross-sectional study was conducted in seven universities from seven geographical regions of Turkey. The study group included 5451 healthcare students. Data were collected with a questionnaire including items on sociodemographic characteristics, vaccination status, knowledge and protective behaviors related to hepatitis B. Data were analyzed with Pearson's chi-square and logistic regression analyses. Results 86.0% of the students had hepatitis B vaccine while 7.6% did not. Vaccination was higher in nursing and midwifery students (aOR = 1.87, CI 95%: 1.26-2.77; aOR = 3.87, CI 95%: 2.14-7.02, respectively). Vaccination was 1.28 times higher in females (CI 95% 1.03-1.60). The ≥23 age group had 1.79 times higher vaccination rate than those in the ≤19 (CI 95%: 1.26-2.53). Vaccination was higher in students whose family's economic status is middle and high (aOR = 1.53, CI 95%: 1.07-2.19; aOR = 1.47, CI 95%: 1.03-2.19, respectively). Vaccination was higher in those living in towns and cities during childhood (aOR = 1.36, CI 95%: 1.06-1.74; aOR = 1.79, CI 95%: 1.34-2.38, respectively). Females had more knowledge of hepatitis B and protective behaviors. Both knowledge and protective behavior scores of vaccinated participants were significantly higher (p < .05). Conclusion We found that the vaccination rate in healthcare students was high, but lower than the country's targets. The students were sensitive about the protective behaviors from hepatitis B infection and had sufficient knowledge of HBV contamination.